Penyalahgunaan Narkoba di Kampung Dalam Pekanbaru - Sugiarto Sugiarto (Pusat Studi Industri dan Perkotaan (PSIP) Universitas Riau, 2011)
The aims of this research are :knowing behavioral appearance background of drugs abuse and factors that influence of drugs abuse in Kampung Dalam, Pekanbaru city. The character of research have descriptive depicted and analyse various mustered data with In-Depth Interview and field observation. Research informan consist of society, drugs abuser, non formal figure as well as formal figure counted 20 people. Thesis consist of 105 page, 49 enclosure list and bibliography and Keyword : deviant behaviour, drugs abuse, defferential association and exchange theory. Based on result of research knowing that, 1) the appearing of disuse in drugs abuse in Kampung Dalam for example : studying process direct and indirectly, interaction process and communication between the actor “ new player” with the boss “ old player” is an interaction process and communication that walk in a long period of time, the relation between the drug user in a very close group due to the trust that has a strong plait, the disuse of drugs by a half of people in Kampung Dalam is a common thing and it is a necessity or the solution of the last work for the people to cover the daily needs. Some not written rules that appear then pre arranged together and become the values to be intent of the people especially the user of drugs in Kampung Dalam in social life. 2) The factors that influenced the disuse of drugs abuse happened in Kampung Dalam, for example : there is a success propotition , if there is a member of drugs mesh that have profit from it, so they will repeat that activity. There is a n impulse proportition that if there is a member of drugs mesh that have recompense or profit from the disusing of the drugs, so they will do the same thing. There is value proportition, if the risk that will they received by the big courier so the recompense that they received are bigger and so on the contrary. There is an agreement proportition and aggression. The agreement is, if the courier do not get the recompense like they hope, for example caught by the police so they will do the agresif act that have a pursue to them like giving information to the police and aggression is the opposite